PEMODELAN DAN PENYELESAIAN PEMROGRAMAN LINEAR DENGAN KOEFISIEN FUNGSI OBJEKTIF BERBENTUK BILANGAN KABUR SEGITIGA - Sani Susanto; Hari Adianto (Majalah Ilmiah Ekonomi Komputer, 2005)
There are three parameters associated with each Linear Programming Model, one of which is the objectivefunction coefficient. This coefficient describes the contribution of one unit of the associate decision variable tothe value of the objective function value. In the traditional Linear Programming Model, it is assumed that thevalues of the objective function coefficients are crisp or certain. This article discuses an approach to formulateand to solve a Linear Programming Model in the case the objective function coefficients are in the form oftriangular fuzzy numberKeywords: Linear Programming Model, Linear Programming Parameter, Fuzzy Number, Objective FunctionCoefficient, Triangular Fuzzy Number